Sosialisasi Pemanfaatan Ikan Laut sebagai Sumber Pangan Kaya Nutrisi di Desa Bilungala, Kecamatan Bonepantai, Kabupaten Bone Bolango - Nurul Fajryani Usman; Devi Bunga Pagalla; Magfirahtul Jannah; Nurhayati Nurhayati (Damhil: Jurnal Pengabdian kepada Masyarakat, 2023)
Gorontalo Province is one of the provinces that has a wealth of natural resources, especially fishery and marine products. One area that has the highest fish production is Bilungala Village, Bone Bolango Regency. Fish is a food rich in protein, minerals, vitamins, and fatty acids. In addition, fish also contain omega-3 fatty acids and vitamin K which the body needs. All the nutritional content in fish is very influential on the growth and development of children. But in fact, the level of fish consumption in Indonesia is still very low compared to other largest fish-producing countries. Therefore, socialization is carried out through the use of marine fish as a source of nutrient-rich food. The purpose of this service is to provide information to the public about the nutritional content of fish, increase fish consumption in the community, and increase the hobby of eating fish. The location of service is carried out in Bulungala Village, Bonepantai District, Bone Bolano Regency, Gorontalo Province. The target of this service is the people of Bilungala Village, especially PKK women with activities carried out in November 2022. The activities consist of the preparation, implementation, and closing stages. In the preparatory stage, a survey was carried out in the village, then in the implementation stage, socialization was carried out to the community through the provision of material and ended with a discussion/question and answer regarding the material presented.